Current theoretical issues of ecological legal order in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2022)
This article discusses current theoretical issues of ecological legal order in the RK. The authors claims that the rule of law is a particularly effective mechanism for increasing the level of environmental awareness of citizens, forcing nature users to comply with the established level of ecological legal order. The scientific novelty of this study is determined by the fact that the paper clarifies and details certain understudied aspects of the concept “ecological legal order”, and also considers ecological legal order as the main ecological and legal institution. The article analyzes that legal order of rational nature management is established under the influence of legislative and other requirements of environmental law. The authors also note that ecological legal order is established on the basis of legal liability. The general trend in developing ecological legal order is to increase social significance of environmental legislation, further modernization of material norms and improving protective forms of their implementation. The purpose of the work is to create a general theoretical and practical concept of ecological legal order in modern Kazakhstan. The authors sets the task to determine the ecological legal order, analyze its place in the field of law, consider the relationship of environmental law and legal responsibility, determine the relationship of environmental legal awareness, education, culture and law and order. The preparation of the work required analysis of prominent research papers, which significantly contributed to development of environmental and legal science.Keywords: ecological legal order, environmental law, legal awareness, norm, environmental legislation, legal relations, law, responsibility